FAKTOR PENGARUH GADGET TERHADAP KECERDASAN MOTORIK SISWA SD MELALUI REGRESI LOGISTIK ORDINAL - Octaviana, Fanny Ayu; Pertiwi, Tutut Januar; Purnama, Giyanti Linda; Hapsery, Alfisyahrina; Yoshinta, Andriana (Program Kreativitas Mahasiswa - Penelitian, 2014)
Gadget is an electronic device that has a specific function and widely used by all people, without exception for kid. Use of gadgets positively has helpful children for homework and as entertaiment. However, without realizing that overusing gadgets have a negative effect.Therefore, the research will be conducted to determine the factors affecting of using gadgets early on the development of motoric intelligence elementary students using ordinal logistic regression.  Source of data used are primary data obtained from the survey, the sampling unit are all mothers who have children in grade 1 SDN Klampis Ngasem I Surabaya. The response variable (Y) is the level of intelligence of the childs motor development (1 = poor, 2 = fair, 3 = good). The results of the analysis, can be concluded that the factors that influence the development of motor 120 students of SDN Klampis Ngasem I Surabaya is long child recognize and use of gadgets every day. Keywords:  Gadgets, Intelligence motoric skills, Logistik Ordinal Regression, Elementary Students.